Restoration of euthyroidism with levothyroxine: implications of etiology of hypothyroidism and the degree of residual endogenous thyroid function - Jonklaas, Jacqueline (Frontiers in Endocrinology, 2022)
There are many thyroid-related factors that combine with non-thyroid-related factors in order to affect the patient response to treatment of hypothyroidism, in terms of their satisfaction with therapy. Some of the thyroid-derived factors include the etiology of the hypothyroidism and the amount of residual thyroid function that the patient retains. These two factors may be intertwined and affected by a third influence, the presence of thyroid peroxidase antibodies. The downstream consequences of the interactions between these three factors may influence both free thyroxine and free triiodothyronine levels, TSH concentrations, and various thyroid biomarkers. Thyroid biomarkers may extend from various well-known products such as lipids and sex hormone-binding globulin to thyroid hormone metabolites and thyroid-regulated genes. Moreover, the interplay between thyroid hormones and biomarkers and their relative ratios may be different depending on the hypothyroidism etiology and degree of residual thyroid function. The ultimate significance of these relationships and their effect on determining patient-reported outcomes, quality of life, and patient satisfaction is, as yet, poorly understood. However, identification of better biomarkers of thyroid function would advance the field. These biomarkers could be studied and correlated with patient-reported outcomes in future prospective studies comparing the impact of various thyroid hormone therapies.